Yoko Ono music of the mind - Bingham, Juliet; Monahan, Connor; Hendricks, Jon 1939- (Tate Publishing, 2024)
"Yoko Ono is an artist who has made an indelible mark on contemporary culture and political activism through her radical and innovative practice. This remarkable and essential publication, developed in collaboration with Yoko Ono and her studio, traces in full the evolution of an artist whose visionary spirit has transcended boundaries and challenged conventions. In Music of the Mind, explore the world of Yoko Ono and discover the profound impact of her art on the collective consciousness of our time."--Cover page [4]
Keywords: Ono, Yōko -- 1933-; Ono, Yōko / Exhibitions; Ausstellungskatalog -- Tate Modern -- 28.09.2024-16.03.2024 -- London; Ausstellungskatalog -- Kunstsammlung Nordrhein-Westfalen, K20 -- 28.09.2024-16.03.2025 -- Düsseldorf; Bildband